SILATURRAHMI DALAM PERSPEKTIF SUNNAH (SUATU KAJIAN HADIS MAUDHU’I DENGAN PENDEKATAN ILMU MA’ANI AL-HADIS) - Firdaus Firdaus; Siar Nimah (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2026)
Silaturahmi (maintaining family and social ties) is a fundamental teaching in Islam that regulates human and social relations. This article aims to analyze the virtues, positive impacts, and threats of severing silaturahmi from the perspective of the hadiths of Prophet Muhammad ﷺ, while reviewing its relevance to modern scientific findings and its contextualization in the digital era. This study employs a qualitative approach with a descriptive-analytical library research method using a thematic hadith approach (maudhu’i) and the science of ma’ani al-hadis. The results indicate that the Prophet's hadiths consistently emphasize the virtues of silaturahmi, such as expanding sustenance, prolonging life, and gaining Allah's assistance. Scientifically, the meaning of "long life" is manifested both qualitatively (the blessings of life) and quantitatively (physical and mental health), which aligns with contemporary research on the positive impact of social relationships on human immunity and life expectancy. Conversely, severing silaturahmi is categorized as a major sin (kaba’ir) with the threat of immediate punishment in this world and being barred from entering heaven. In the modern era, the essence of silaturahmi can still be maintained through digital media as a solution to overcome distance barriers without diminishing the substance of human values taught by the sunnah.